Electronic finance a new perspective and challenges. - Monetary and Economic Department, Bank for International Settlements (Basel : Bank for International Settlements., 2001)
This publication is based on the presentations given during a workshop on electronic finance convened by the BIS on 2-3 July 2001. The individual papers cover, inter alia, trading in wholesale financial markets, emerging competition in the payment system and the progress of virtual banks. Implications for financial supervision and monetary policy are also specifically addressed in separate papers. As there are a plethora of technical terms associated with the subject, a glossary is included at the end of this volume.
lje 10/08/16
Ref
Keywords: Electronic funds transfer; Payment systems